A smart sustainable city: The challenges facing sustainable mobility - Kauf, Sabina (Zrównoważona mobilność jako wyznacznik smart city, 2019)
The article presents issues related to creating sustainable mobility, which is one of the main elements of a smart city, the understanding of which in recent years has changed dramatically. We can observe a departure from the strictly technological understanding of a smart city, in favour of creative development and providing incentives for shaping urban space that is not only public, but also respects the requirements of the environment. This aspect is also necessary for the development of smart and sustainable mobility. The aim of this study is to identify the main premise and the characteristics of a smart and sustainable city, and to present mobility as one of the key challenges involved in the operationalization of the concept. Although the issue of a smart city and sustainable city in the literature is often taken up, their combination is less explored. These considerations start with presenting the key components of a smart sustainable city. This will allow to understand the idea of the concept. Next, we will go to the issue of mobility, which plays an important role in creating a smart sustainable city
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 230-243
Keywords: sustainability; smart city; smart mobility; zrównoważony rozwój; inteligentne miasta; inteligentna mobilność